Perlindungan Hukum bagi Pemilik Bangunan atas Tanah yang Dijaminkan pada Bank yang Telah Dilikuidasi: Studi Kasus Putusan PT Medan Nomor 293/Pdt/2018/PT-Mdn - Muhammad Luthfiadi Akbar; Muhammad Yamin; Tengku Keizerina Devi Azwar (Jurnal Hukum Lex Generalis, 2026)
Legal protection for building owners on land encumbered as collateral at a liquidated bank constitutes an important issue in land law practice, as reflected in the Medan High Court Decision Number 293/Pdt/2018/PT-Mdn. The issues examined include the relationship between the principal obligation and mortgage rights, the status of collateral after debt settlement through subrogation and administrative obstacles in the discharge of mortgage (roya). The study employs a normative juridical method with a case approach. The results indicate that although the debt has been settled, the mortgage has not been administratively discharged, creating legal uncertainty. The court provides protection to good faith buyers through recognition of rights, transfer of documents and the completion of land administration.